Unveiling The Hidden Threat: Exploring the Diagnostic Prowess of MRI in Detecting Post-Laminar Optic Nerve Invasion in Retinoblastoma Patients - a Meta-Analysis - Ahmadi Putri, Nabila Maharani; Pratama, MR; Ayuputri, AN (Pelopor Publikasi Akademika, 2025)
Retinoblastoma (RB), a rare and aggressive intraocular malignancy, is a devastating pediatric cancer primarily affecting the retina, with a global incidence of approximately 1 in 15,000 live births. The use of preoperative magnetic resonance imaging (MRI) to identify post-laminar optic nerve invasion (PLONI) is believed to be useful for planning therapeutic approaches. This study aims to determine the diagnostic performance of MRI in identifying PLONI in retinoblastoma patients. This study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020. Systematic search was conducted in several international databases including Google Scholar, PubMed, EBSCOhost, and Proquest from earliest entry to 2023. The quality of studies was assessed using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS) criteria. Sensitivity and specificity values were extracted from each study and meta-analysis of the pooled sensitivity and specificity were calculated using STATA 17. Seventeen studies were eligible for the meta-analysis. Based on the meta-analysis of the included studies, the authors found that the overall sensitivity was 69,0% (95%CI: 58%-80%), overall specificity was 80,0% (95%CI: 73%-87%), and exhibited a notable heterogeneity (I2 = 85,5%). MRI has high specificity in identifying PLONI in RB, so it can be used as a diagnostic modality, especially in cases where eye-preserving therapy is taken into consideration.